Development of an Infrared-assisted Pneumatic Paddy Drying System - Sila, Boontarika; Treeamnuk, Krawee; Treeamnuk, Tawarat (RMUTP Research Journal Sciences and Technology, 2024)
The development of various dryers to dry paddy still faces a significant problem of high energy consumption. Therefore, this research objective was to develop an infrared-assisted pneumatic paddy drying system and study the possibility of reducing the problem. The study consists of 3 methods of drying paddy, namely: 1) drying paddy by hot air 60°C; 2) drying paddy by hot air 60°C with 50 W infrared radiation; and 3) Drying paddy with 800 W infrared radiation. In this study, 20 kg of Thai jasmine 105 paddy with initial moisture content 23%w.b. was dried until 14%w.b. at drying air velocity and paddy feed of 6 m/s and 8.4 kg/min respectively. The performance of drying was evaluated based on the drying characteristic curve, drying rate and the specific energy consumption (SEC) of the developed drying system. The results showed that hot air combined with infrared radiation in drying had fastest time 220 min in drying. Drying rate of hot air drying and hot air drying combined with infrared radiation was no statistical difference (p<0.05). The lowest SEC was 14.24 ± 0.88 MJ/kg water and it was not significantly different (p<0.05) when comparing within all experiment methods.